Personal best time, percent body fat, and training are differently associated with race time for male and female Ironman triathletes - Knechtle, B.; Wirth, A.; Baumann, B.; Knechtle, P.; Rosemann, T. (Research Quarterly for Exercise and Sport, 2010)
We studied male and female nonprofessional Ironman triathletes to determine whether percent body fat, training, and/or previous race experience were associated with race performance. We used simple linear regression analysis, with total race time as the dependent variable, to investigate the relationship among athletes' percent body fat, average amount of weekly training, and best time in an Ironman triathlon. For male athletes, percent body fat (r2 = 0.57, p < .001) was related to total race time but not average weekly training. For women, percent body fat showed no association with total race time; however, average weekly training volume was related to total race time (r2 = .43, p < .01). Percent body fat and average weekly training were not correlated in either gender. Speed in training was not associated with race performance in either gender. For men (r2 = .56, p < .001) and women (r2 = .45, p < .05), personal best time in an Ironman triathlon was related to total race time. We concluded that percent body fat was related to race performance in male athletes and to average weekly training in female athletes. Personal best time in an Ironman triathlon was associated with total race time for both male and female athletes.